Sexist stereotypes in the language textbooks of the Greek primary school: a multidimensional approach. Issue 5 (4th July 2018) - Gouvias, Dionysios; Alexopoulos, Christos
ABSTRACT: School textbooks are the main means of instruction and the main tool for the organisation of the teachers' pedagogic practices. Stereotypes concerning the two genders are inscribed in the curriculum and become evident inside the school textbooks. The present study, through a content analysis of the Greek-language textbooks used in the third grade of the Greek primary school, examines the existence of gender stereotypes throughout the full range of these books. Additionally, semi-structured interviews with a sample of teachers who have taught the particular subject in the past are carried out. The findings show that there is a need for evaluation of the existing language textbooks in primary schools, with the aim of promoting a more gender-balanced learning material. Moreover, the classroom teachers raise the need for the promotion of initial as well as in-service training for teachers on issues of 'gender stereotypes', 'language sexism' and 'gender-mainstreaming policies'.